Correlation of sarcopenia and depressive mood in older community dwellers: a cross-sectional observational study in China. Issue 9 (1st September 2020) - Chen, Lei; Sheng, Yunlu; Qi, Hanmei; Tang, Tingting; Yu, Jing; Lv, Shan
Abstract : Objective: Whether sarcopenia is detrimental to depression is still controversial, which may be due to the three components of the sarcopenia. Our objective was to define the correlation between depression and sarcopenia in older Chinese community dwellers. Design: The study has a cross-sectional design. Setting: The study was conducted in Jiangsu, China. Participants: A total of 101 men and 149 women aged 60 years or older were recruited. Outcome measures: Lean tissue mass was measured by dual-energy X-ray absorptiometry. Muscle strength in the upper and lower limbs was measured by a handheld dynamometer and a chair stand test, respectively. Physical performance was assessed by gait speed and standing balance tests. Depressive mood was assessed using the Geriatric Depression Scale-30 (range 0–30). Results: Participants in the sarcopenia group had a higher mean depression score than the normal group (p=0.002). Pearson's correlation analysis showed that depression was negatively associated with muscle strength (handgrip strength: R=−0.170, p=0.028 for women, R=−0.196, p=0.048 for men; chair stand test performance: R=0.252, p=0.002 for women, R=0.311, p=0.001 for men) and physical performance (gait speed: R=−0.200, p=0.009, standing balance test performance: R=−0.224, p=0.006, Short Physical Performance Battery (SPPB): R=−0.218, p=0.007 for women; SPPB: R=−0.252, p=0.01 for men). Multiple linear regression models revealed that depressive mood was inversely associated with chair stand test (β = 0.325, p<0.001), gait speed (β = −0.009, p=0.041) and standing balance test (β=−0.24, p=0.016) after adjusting for confounding factors, while no significant correlation was observed between depressive mood and muscle mass. Conclusion: The diagnostic components of sarcopenia—strength of the leg muscles (chair stand test) and physical performance (gait speed and standing balance test)—were associated with depressive mood.